A retrospective study on parapneumonic effusion in 130 dogs with a clinical diagnosis of pneumonia - Burnotte, Priscilla; Graziano, Nicolas; Gommeren, Kris (Frontiers in Veterinary Science, 2023)
Objective: To screen the occurrence of parapneumonic effusion in dogs. Design: Medical records were searched for dogs with a presumptive diagnosis of bacterial pneumonia from 2017 to 2021 at the Liege university teaching hospital. Bacterial pneumonia was presumptively diagnosed based on compatible clinical signs and findings; thoracic radiographs compatible with bacterial bronchopneumonia; and either increased serum C-reactive protein (CRP) levels, a positive bronchoalveolar lavage culture or a positive clinical evolution in response to antibiotic therapy. Patients diagnosed with parasitic or other non-bacterial inflammatory pneumonia or with pulmonary neoplasia were excluded. Signalment, clinical findings, and outcome were recorded. Results: One hundred and thirty dogs were included in the study, of which 44 dogs (33,8%) developed a parapneumonic effusion. Four of these dogs (4/44; 9%) had thoracocentesis performed, displaying a modified transudate (2) or septic exudate (2). Conclusions: Although parapneumonic effusion in dogs with a presumptive diagnosis of bacterial pneumonia appears to be rather common (33.8%), thoracocentesis or chest tube placement was rarely performed. Furthermore, the outcome of dogs with and without parapneumonic effusion appears to be similar.